Distribution of Optimized Public Assets Utilization in Yogyakarta Province - Khoirudin, Rifki; Wahyuni, Sri; Nugraha, Catur Budi (Jurnal Analisis Bisnis Ekonomi, 2021)
Public asset is an integral part of regional assets that is owned and controlled by regional government, this asset could be financed partly or wholly by regional budget. Asset should be distributed proportionally to optimally support the economic development. This study examines the distribution of assets to boost regional economic growth that eventually will increase the regional government revenue. The optimized distribution of public assets is expected to be a source of regional financing and asset management is one of the keys to successfully manage regional economic. The conclusion is that the asset management with innovation and technology could optimize the utilization of regional assets in boosting the economy.